High-rate OVPE-GaN growth by the suppression of polycrystal formation with additional H2O vapor in a high-temperature condition. (27th August 2020) - Shimizu, Ayumu; Tsuno, Shintaro; Kamiyama, Masahiro; Ishibashi, Keiju; Kitamoto, Akira; Imanishi, Masayuki; Yoshimura, Masashi; Hata, Masahiko; Isemura, Masashi; Mori, Yusuke
Abstract: The oxide vapor phase epitaxy (OVPE) method enables the fabrication of low-resistivity GaN crystals. However, polycrystal formation is detrimental to the growth of thick GaN crystals at the high growth rate by the OVPE method. In this study, we focused on H2 O additive under the high-rate and high-temperature growth condition to suppress generation of Ga droplet, the origin of polycrystalline GaN. The polycrystal density dramatically decreased by adding H2 O, which can convert Ga droplet into Ga2 O vapor. We obtained a 431 μ m thick OVPE-GaN layer at 108  μ m h −1, which is the highest value in GaN crystals grown by the OVPE method.